2015
DOI: 10.1189/jlb.3a0415-157r
|View full text |Cite
|
Sign up to set email alerts
|

Complement anaphylatoxin receptors C3aR and C5aR are required in the pathogenesis of experimental autoimmune uveitis

Abstract: Recent studies have suggested that reagents inhibiting complement activation could be effective in treating T cell mediated autoimmune diseases such as autoimmune uveitis. However, the precise role of the complement anaphylatoxin receptors (C3a and C5a receptors) in the pathogenesis of autoimmune uveitis remains elusive and controversial. We induced experimental autoimmune uveitis in mice deficient or sufficient in both C3a and C5a receptors and rigorously compared their retinal phenotype using various imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…For example, Ccl5 was regulated in a Card9-dependent fashion within the retina and CCL5 (RANTES) has been found to activate CCR5 on T cells to promote EAU (31). The anaphylaxins C3a and C5a, whose induction was also regulated by Card9, were recently shown to contribute to EAU through promotion of the Th17 response (32). Taken together, these data identify an important role for Card9 in induction of genetic responses and pathways relevant to the Th17 cell response, which is an underlying mechanism of EAU.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ccl5 was regulated in a Card9-dependent fashion within the retina and CCL5 (RANTES) has been found to activate CCR5 on T cells to promote EAU (31). The anaphylaxins C3a and C5a, whose induction was also regulated by Card9, were recently shown to contribute to EAU through promotion of the Th17 response (32). Taken together, these data identify an important role for Card9 in induction of genetic responses and pathways relevant to the Th17 cell response, which is an underlying mechanism of EAU.…”
Section: Discussionmentioning
confidence: 99%
“…EAU induction was conducted following the established method. 10,17,18 Briefly, mice were immunized with an emulsion of complete Freund's adjuvant with 2 mg/ml desiccated Mycobacterium tuberculosis (Sigma-Aldrich, St Louis, MO, USA) and 300 lg human interphotoreceptor retinoidbinding protein (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The mice received a subcutaneous injection of the emulsion (200 ll) into three sites on the lower back, followed by an intraperitoneal injection of 0Á3 lg pertussis toxin.…”
Section: Mice and Eau Modelmentioning
confidence: 99%
“…A few studies have already reported involvement of the complement cascade in uveitis development [53][54][55], as well as in EAE pathogenesis [56].…”
Section: Discussionmentioning
confidence: 99%